Representation of the educational model based on caring for self and others, in Surah Al-Furqan; Emphasizing the views of Ayatollah Javadi Amoli - fatemeh vojdani; Seyyede Masoume Mousavi (اخلاق وحیانی, 2022)
Because a large part of human learning is through implicit and observational learning, the modeling method, including model-making, is one of the important educational methods. Mode-making, like all elements of an educational program, must be appropriate to the indigenous culture of each country. Hence, the Holy Quran can be used as a rich and inspiring source in this regard. The final verses of Surah Al-Furqan have modeled Ibad al-Rahman as a model for good people. The purpose of this study was to represent this model using the interpretations of the Holy Quran, especially Tasnim. The research method is descriptive-analytical. According to the findings, the basic characteristics of Ibad al-Rahman include three characteristics: servitude, mercy and patience; which in detail expands to 20 characteristics. There are 7 characteristics related to self-care about spiritual development and 13 characteristics related to caring for others’ spiritual development. The privileged servants of God are constantly taking care of themselves and others. More precise examples for caring are explained under three headings in this article.